Agrobiodiversity solution hotspot tool: IPSR Innovation Profile - Jones, Sarah K.; Estrada-Carmona, Natalia; Sharma, Sunaya (2022)
An agrobiodiversity solution hotspot tool will improve understanding of relationships across the food system and help identify priority interventions to restore and enhance ecosystem functions and services for sustainable social and economic benefits. A spatially explicit water, energy, food, and environment (WEFE) threat analysis will be conducted for the focal landscape of the Ganges Basin. Findings will be used to co-develop and co-create a downscaled Agrobiodiversity Index approach, through which integrated agrobiodiversity-based solutions will be identified with local stakeholders to address WEFE challenges in all NEXUS Gains basins. For this, we will apply a locally relevant, practical methodology for prioritizing where, and deciding how, to enhance agrobiodiversity to improve the sustainability and resilience of agricultural and food production systems. Intensive collaboration will take place with local and national research and government partners, initially in India and expanding to Pakistan and Nepal, to co-develop, test, modify and improve the proposed approach and support systems-oriented decision making and integrated and locally relevant scenario and model development.